2017
DOI: 10.1634/theoncologist.2016-0298
|View full text |Cite|
|
Sign up to set email alerts
|

The Use of Hyperbaric Oxygen for the Prevention and Management of Osteoradionecrosis of the Jaw: A Dana-Farber/Brigham and Women’s Cancer Center Multidisciplinary Guideline

Abstract: Background. Osteoradionecrosis of the jaw (ORN) is an infrequent yet potentially devastating complication of radiation therapy to the head and neck region. Treatment options include antimicrobial therapy, local sequestrectomy, resection, and the use of hyperbaric oxygen (HBO). Published data on ORN are difficult to compare because of the lack of a universally accepted classification and staging system, and the literature on the use of HBO to either prevent or successfully manage ORN is controversial and inconc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 41 publications
(92 reference statements)
0
57
0
2
Order By: Relevance
“…Therefore, during this period, we kept monitoring blood glucose levels without additional work. Nonetheless, the protocol of establishing a STZ-induced diabetic rat model has been widely applied in the wound healing studies of diabetic foot ulcers, as supported by the following references (Table S1) [10][11][12][13][14][15][16][17]. Then, a wound (5 × 5 mm) was created in the left forepaw of each rat after anesthetizing with sodium pentobarbital (45 mg/kg body weight) by intraperitoneal injection.…”
Section: Animal Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, during this period, we kept monitoring blood glucose levels without additional work. Nonetheless, the protocol of establishing a STZ-induced diabetic rat model has been widely applied in the wound healing studies of diabetic foot ulcers, as supported by the following references (Table S1) [10][11][12][13][14][15][16][17]. Then, a wound (5 × 5 mm) was created in the left forepaw of each rat after anesthetizing with sodium pentobarbital (45 mg/kg body weight) by intraperitoneal injection.…”
Section: Animal Modelmentioning
confidence: 99%
“…Hypoxia is a key inhibiting factor for wound healing of DFUs, which can block fibroblast proliferation, collagen production, and capillary angiogenesis and enhance the risk of infection [8][9][10]. Hyperbaric oxygen therapy (HBOT) is the most commonly utilized adjunctive therapy for improving wound tissue hypoxia in DFU treatment [11][12][13], but this method has not achieved universal success in many studies and is costly [14,15]. And the production of HBO-related oxidative stress is a concern [16].…”
Section: Introductionmentioning
confidence: 99%
“…The Division of Head and Neck Oncology of Dana-Farber/Brigham and Women’s Cancer Center, USA does not recommend the routine use of hyberbaric oxygen therapy for the prevention or management of osteoradionecrosis and they recommend adjunctive hyberbaric oxygen therapy in exceptionally high risk cases where there is failed history of conservative therapy and subsequent surgical resection. 6 …”
mentioning
confidence: 99%
“…Some reports have recommended clodronate for ORN owing to its effect on osteoclast inhibition, but evidence supporting its usefulness is insufficient [6]. In addition, hyperbaric oxygen therapy was reported to be an excellent adjunct treatment for ORN, as it stimulated angiogenesis, fibroblast, and collagen formation [20]. Khorsandi also reported that hyperbaric oxygen therapy is associated with significantly improved clinical and radiographic outcomes for a patient with cervical ORN [11].…”
Section: Discussionmentioning
confidence: 99%